The role of imports, exchange rates, and reserve stability in driving Indonesia’s export performance - Azmi Fawwaz Syahrullah; Adang Djatnika Effendi; Herry Sutanto (Universitas Ahmad Dahlan, 2026)
Indonesia’s export performance is shaped by various macroeconomic factors that represent both the country’s production capabilities and broader external economic conditions. This study explores how exchange rates, imports, and foreign exchange reserves influence Indonesia’s export activities. In contrast to many earlier studies that examined these variables individually, this research brings them together in one empirical framework to better understand their joint impact on export performance. The analysis is based on annual time-series data from 1995 to 2024, sourced from the World Bank database. The Autoregressive Distributed Lag (ARDL) model is applied to identify both short-run dynamics and long-run relationships among the variables. Prior to estimation, several econometric procedures are conducted, including unit root testing, optimal lag selection based on the Akaike Information Criterion, bounds testing for cointegration, and diagnostic tests to ensure model reliability. The empirical findings indicate that imports have a positive and statistically significant impact on Indonesia’s exports in both the short term and the long term. Meanwhile, the exchange rate does not appear to have a significant direct influence on export performance. Foreign exchange reserves, on the other hand, show a positive relationship with exports, although the statistical strength of this effect is relatively weaker. Overall, these results suggest that ensuring the availability of imported production inputs and maintaining macroeconomic stability are important factors in supporting sustainable export growth in Indonesia.